Failure to relax negative supercoiling of DNA is a primary cause of mitotic hyper-recombination in topoisomerase-deficient yeast cells. - Trigueros, S; Roca, J (2002)
In the yeast Saccharomyces cerevisiae, DNA topoisomerases I and II can functionally substitute for each other in removing positive and negative DNA supercoils. Yeast Delta top1 top2(ts) mutants grow slowly and present structural instability in the genome; over half of the rDNA repeats are excised in the form of extrachromosomal rings, and small circular minichromosomes strongly multimerize. Because these traits can be reverted by the extrachromosomal expression of either eukaryotic topoisomerase I or II, their origin is attributed to the persistence of unconstrained DNA supercoiling. Here, we examine whether the expression of the Escherichia coli topA gene, which encodes the bacterial topoisomerase I that removes only negative supercoils, compensates the phenotype of Delta top1 top2(ts) yeast cells. We found that Delta top1 top2(ts) mutants expressing E. coli topoisomerase I grow faster and do not manifest rDNA excision and minichromosome multimerization. Furthermore, the recombination frequency in repeated DNA sequences, which is increased by nearly two orders of magnitude in Delta top1 top2(ts) mutants relative to the parental TOP+ cells, is restored to normal levels when the bacterial topoisomerase is expressed. These results indicate that the suppression of mitotic hyper-recombination caused by eukaryotic topoisomerases I and II is effected mainly by the relaxation of negative rather than positive supercoils; they also highlight the potential of unconstrained negative supercoiling to promote homologous recombination.